Blockchain Technology for Sustainable Waste Management - Taylor, Phillip; Steenmans, Katrien; Steenmans, Ine (Frontiers in Political Science, 2020)
The global waste and resource crises necessitate and give great impetus for better and more sustainable management of waste. Increasingly, resource and waste streams that once were sent to landfill or incinerated are now reused, recycled, or recovered. Yet, while many laws and policies have been adopted for this very purpose, a number of recurrent challenges persist across interventions seeking to further facilitate the necessary, widespread transitions to sustainable waste management. This perspective article explores the suitability of blockchain technology in overcoming these challenges. In particular, we discuss the opportunities and challenges for blockchain in (1) offering clarity in property rights of products and wastes, (2) supporting law and policy goals by incentivising sustainable waste management, and (3) maintaining anonymity and privacy for institutions and individuals.